The Power of Genre - Rosmarin, Adena (Book collections on Project MUSE., 1985)
The Power of Genre was first published in 1986. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. The Power of Genre is a radical and systematic rethinking of the relationship between literary genre and critical explanation. Adene Rosmarin shows how traditional theories of genre-whether called "historical," "intrinsic," or "theoretical"--Are necessarily undone by their attempts to define genre representationally. Rather, Rosmarin argues, the opening premise of critical argument is always critical purpose or, as E.H. Gombrich has said, function, and the genre or "form" follows the reform. The goal is a relational model that works. Rosemarin analyzes existing theories of genre - those of Hirsch, Crane, Frye, Todorov, Jauss, and Rader are given particular attention-before proposing her own. These analyses uncover the illogic that plagues even sophisticated attempts to treat genre as a preexistent entity. Rosmarin shows how defining genre pragmatically - as explicitly chosen or devised to serve explicitly critical purposes - solves this problem: a pragmatic theory of genre builds analysis of its metaphors and motives into its program, thereby eliminating theory's traditional need to deny the invented and rhetorical nature of its schemes. A pragmatic theory, however, must be tested not only by its internal cohesion but also by its power to enable practice, and Rosmarin chooses the dramatic monologue, an infamously problematic genre, and its recent relative, the mask lyric, as testing grounds. Both genres-variously exemplified by poems of Browning, Thennyson, Eliot, and Pound-are ex post facto critical constructs that, when defined as such, make closely reasoned sense not only of particular poems but also of their perplexed interpretive histories. Moreover, both genres dwell on the historicity, textuality, and redemptive imperfection of the speaking self. This generic obsession ties the poems to their reception and, finally, to the openended, processes of hermeneutic question-and-answer stressed in Rosmarin's framing theory